Sensory Evaluation And Acceptability Of Bambusa Blumeana As Bamboo Shoot Polvoron - Ruby D. G. Elumbra (International Journal of Advanced Science and Technology, 2020)
The Bamboo shoots of the grassy Poacaea family have fiber, potassium and lignans, which are believed to hold anti-cancer, antibacterial, anti-fungal and anti-viral properties, according to agsyt.wsu.edu. There is a legion of studies, which pertain to the use of bamboo shoots as the main ingredients in baked goods. An example is the Polvoron which is one of the popular desserts of Filipinos especially among young ones. This study present a new flavor of polvoron derived from the bamboo shoot powder. The product also underwent nutritional analysis that was conducted by the Food and Nutrition Research Institute Service Laboratory in Manila.  This study aimed to develop processed bamboo shoot into polvoron along with its sensory evaluation and acceptability among consumers. The researchers used an experimental design for the four treatments with different measurement of bamboo shoot powder for every treatment employed during the evaluation. There are  50  untrained respondents. Respondents were able to select and evaluate the products using the Semantic scale for the color, taste and texture and hedonic scale and facial hedonic scale for the  general acceptability of the product. Results showed that Treatment 3 had the most acceptable treatment with a mean value of 7.95, interpreted as  Like Very Much with  light  brown,  pronounced bamboo shoot flavor, moderately smooth texture and moderately detected bamboo shoot odour.  Hence the incorporation of powdered bamboo shoots into polvoron is widely acceptable among its consumers.